A high-fidelity wave-to-wire simulation platform for wave energy converters: Coupled numerical wave tank and power take-off models. (15th September 2018) - Penalba, Markel; Davidson, Josh; Windt, Christian; Ringwood, John V.
Highlights: A novel high-fidelity simulation platform is presented coupling CFD and a PTO model. CFD-based approaches are reinforced for applications where high-fidelity is vital. Significant overestimation is observed for excessively simplified PTO models. Minor inaccuracies in a conversion stage can significantly affect the power estimate. Abstract: Performing rigorous technical and commercial assessment of wave energy converters (WECs) numerically, before engaging in expensive wave tank and open ocean tests, is vital for the economically successful development of prototypes. To that end, this paper presents a high-fidelity wave-to-wire simulation platform (the HiFiWEC ), where a Computational Fluid Dynamics (CFD)-based numerical wave tank is coupled to a high-fidelity power take-off (PTO) model, which enables assessment of WEC performance with greater accuracy than with previous wave-to-wire approaches. A test case, simulating the performance of a heaving point absorber type WEC in realistic conditions, is presented and compared against traditional lower fidelity modelling methods. The WEC response is evaluated with a number of different approaches, including different techniques to model hydrodynamic wave-structure interactions and the power take-off system, and the benefits of the HiFiWEC are highlighted. The results highlight that excessive simplifications in the modelling of the PTO system can lead to significant overestimation in generated energy output, with relative deviations ( ∊ ) of up to 150% compared to the HiFiWEC . In addition, uncertainty in viscous drag parameters added to hydrodynamic models based on boundary element method solvers, reinforce the necessity of CFD-based models for applications where high-fidelity is essential. Finally, it is demonstrated that minor/insignificant inaccuracies in the hydrodynamic model ( ∊ = 0.5 % ) can result in significant differences in the estimation of the final energy generation ( ∊ = 7 % ), highlighting the need for a coupled high-fidelity platform.